Distinct transcription factor interactions drive HOXB13 activity in different stages of prostate cancer - Betul Ersoy-Fazlioglu; Shreyas Lingadahalli; Umut Berkay Altintas; Ahmet Cingoz; Emirhan Tekoglu; Ivan Pak Lok Yu; Meric Dikbas; Olka Missaghimamaghani; Kerim Yavuz; Hans Adomat; Ibrahim Kulac; Tunc Morova; et al. (Proceedings of the National Academy of Sciences, 2025)
HOXB13 is a lineage-specific transcription factor that plays a critical role in initiation and progression of prostate cancer (PCa). While most research has focused on the role of HOXB13 on androgen receptor (AR) activity, here we demonstrate that HOXB13 is frequently expressed in AR-negative tumors and is essential for the proliferation of both AR-positive and -negative PCa models. Strikingly, HOXB13 is remarkably selective and has almost no effect on nonprostatic tissues. Despite this common essentiality in PCa, HOXB13 activity is markedly different in AR-negative stem cell–like tumors, where interactions with the AP-1 change the HOXB13 cistrome and interactome. Yet despite these distinct activities, HOXB13 activity is commonly mediated by SMARCD2, a member of the mSWI/SNF chromatin remodeling complex. The HOXB13/SMARCD2 interaction alters chromatin accessibility at HOXB13-binding sites, causing increased proliferation in AR-negative PCa. Overall, this work demonstrates a distinct mechanism of action for HOXB13 and highlights its critical role in AR-negative castration-resistant PCa.